2016
DOI: 10.5606/ehc.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical and radiological outcomes of open reduction via medial and anterior approach in devleopmental dysplasia of the hip

Abstract: ÖZ Amaç:Bu çalışmada gelişimsel kalça displazisi (GKD) nedeniyle medial veya anterior yaklaşımla açık redüksiyon uygulanan çocuklarda cerrahi yaklaşımın klinik ve radyolojik sonuçlar, avasküler nekroz (AVN) insidansı ve revizyon cerrahisi gerekliliği üzerindeki etkileri araştırıldı. Hastalar ve yöntemler: Ocak 1997 -Aralık 2010 tarihleri arasında GKD tedavisi yapılan, en az dört yıl düzenli takip edilen ve son kontrolde beş yaş ve üzerinde olan 36 hastanın (9 erkek, 27 kız; ort. yaş 13.8 ay; dağılım 6-18 ay) 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…In this step, the iliopectineal ligaments stands as a safeguard against reaching the femoral vessels and preventing their iatrogenic injury. These facts were supported also by Glorion, C. et al (16,17) , Weinstein, S. L. et al [18] and Yorgancigil, H. el al [19].…”
Section: Morphological Findingssupporting
confidence: 63%
“…In this step, the iliopectineal ligaments stands as a safeguard against reaching the femoral vessels and preventing their iatrogenic injury. These facts were supported also by Glorion, C. et al (16,17) , Weinstein, S. L. et al [18] and Yorgancigil, H. el al [19].…”
Section: Morphological Findingssupporting
confidence: 63%
“…Tenotomy of the psoas tendon not only eliminates a structure that prevents reduction on the capsule but also prevents the development of avascular necrosis and re-dislocation after reduction. [ 15 ] Data about the tenotomy of the on the outcomes of the iliopsoas tendon tenotomy are rather is limited. The first publication in the literature was by Basset et al[ 8 ] in 1999.…”
Section: Discussionmentioning
confidence: 99%
“…The AVN rate in this study was 15.3% (12/78), relatively lower than most of the other studies. Ning et al [21] Binnet et al [24] and Yorgancıgil et al [25] suggested that AVN rates increased with a preoperative Tönnis dislocation grade increase. The mean period of follow-up was relatively short (26.5 ± 6.9 months); hence, we may not have identified patients with developing osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%